Globalization, social capital and inequality : contested concepts, contested experiences - Dolfsma, Wilfred; Dannreuther, Charlie; European Association for Evolutionary Political Economy (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
This work investigates the relationship between globalization, inequality and social capital, revealing that although related, these ideas are also contested. The authors elucidate the interactions between these concepts, looking at the conflicts and competitiveness which can arise.
Includes bibliographical references and index.
rpm 22/09/16
Loans
Keywords: International economic integration; Globalization; Equality; Social capital (Sociology)